CT pulmonary angiography in patients with acute or chronic renal insufficiency: evaluation of a low dose contrast material protocol - Meyer, Mathias; Haubenreisser, Holger; Schönberg, Stefan; Henzler, Thomas (Scientific reports, 2018)
Adverse effects of intravenous contrast media (CM) in patients with renal risk factors and acute kidney injury are still controversially discussed. The aim of this study was to investigate whether dual-energy (DE) pulmonary CT angiography (CTPA) in combination with a noise optimized virtual monoenergetic imaging algorithm allows for a reduction of CM. This IRB-approved study comprised 150 patients with suspected pulmonary embolism (78 male; mean age 65 ± 17years). 50 patients with acute/chronic renal failure were examined on a 3rd generation dual-source CT with an optimized DE CTPA protocol and a low CM injection protocol (5.4 g iodine). 100 further patients were either examined with a standard CTPA protocol or a standard DE CTPA (32 g iodine). For the DE CTPA virtual monoenergetic spectral datasets (40-100 keV) were reconstructed. Main pulmonary arteries at 50 keV and peripheral pulmonary arteries at 40 keV datasets provided the highest contrast-to-noise-ratio (CNR) for both the standard DE CTPA and the optimized protocol, with significantly higher CNR values for the standard DE CTPA protocol (p < 0.05). No pulmonary embolism was missed on the optimized CM protocol. DE CTPA utilizing image reconstruction at 40/50 keV allowed for a reduction of 84% in iodine load while maintaining CNR, which is especially important in patients with acute/chronic renal failure.
Gesehen am 17.09.2019